2010
DOI: 10.1097/nrl.0b013e318198d8bc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Activation, Coagulation, and Fibrinolytic Activation in Patients With Symptomatic Lacunar Stroke

Abstract: Different hemostatic factors may play a role in the pathogenesis of lacunar stroke. Evaluating the role of hemostatic factors on different types of strokes may help us identify new therapeutic strategies and different prognostic stratifications for ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…A total of 7 studies were included [24,25,26,27,28,29,30] (336 lacunar strokes) but available data did not permit meta-analysis. Jood et al [26] report levels of PAI significantly higher in lacunar stroke versus non-stroke controls acutely and chronically.…”
Section: Plasma Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 7 studies were included [24,25,26,27,28,29,30] (336 lacunar strokes) but available data did not permit meta-analysis. Jood et al [26] report levels of PAI significantly higher in lacunar stroke versus non-stroke controls acutely and chronically.…”
Section: Plasma Markersmentioning
confidence: 99%
“…Here, 9 studies were included [25,30,32,34,37,38,39,40,41] (364 lacunar strokes) of which 4 could be meta-analysed (fig. 2).…”
Section: Plasma Markersmentioning
confidence: 99%
“…Slavka et al (16) concluded that patients with increased MPV values (≥11.01 fL) were at a higher risk of ischemic heart disease. Ilhan et al (17) found a significant difference in MPV levels between patients with symptomatic lacunar stroke infarcts and controls (p<0.01). Mayda-Domac et al (18) observed that MPV was an independent risk factor for ischemic stroke (p=0.007) and hemorrhagic stroke (p=0.001).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, other authors claim that the mean platelet volume is unrelated to stroke severity and subtype [27]. From the literature it also appears that lacunar strokes are associated with increased platelet activity [25] and that circulating P-selectin increases in large-vessel infarctions [28].…”
Section: Introductionmentioning
confidence: 96%
“…In acute stroke, concentrations of the protein appear to increase [6]. Still, other scientists have been unable to demonstrate soluble P-selectin alterations in stroke [25]. Even fewer studies have been devoted to platelet alterations in different stroke subsets.…”
Section: Introductionmentioning
confidence: 99%